Corrosion fatigue behavior of Ti-6Al-4 V: Chemical and mechanical driving forces. (July 2018) - Baragetti, S.; Arcieri, E.V.
Highlights: Analyses about the SCC and corrosion fatigue behavior of Ti-6Al-4 V were carried out. A chemical and a mechanical driving force were identified. Air and paraffin oil have the same effects, NaCl solution gives a small reduction. Methanol has detrimental effects even for small concentrations in fatigue tests. Aggressive media + cyclic loads are more detrimental than only aggressive media. Abstract: The high strength-to-mass ratio and the appreciable corrosion resistance make the Ti-6Al-4 V alloy used in aerospace, automotive, maritime and biomedical applications. In this work the quasi-static behavior of this light alloy and its axial fatigue resistance in air, air + beeswax coating, paraffin oil, 3.5 wt% NaCl solution and various water-methanol solutions are presented in order to understand the effects of the medium and of the load. The contribution of the stress concentration factor K t, calculated by means of finite element modelling, is investigated. A SEM (scanning electron microscopy) analysis was carried out in order to evaluate the microstructural modifications due to the environments and cyclic loads.